2008
DOI: 10.1111/j.1472-765x.2008.02360.x
|View full text |Cite
|
Sign up to set email alerts
|

Petite mutation in aged and oxidatively stressed ale and lager brewing yeast

Abstract: Aims:  To determine the role of oxidative stress and chronological ageing on the propensity of brewing yeast strains to form respiratory deficient ‘petites’. Methods and Results:  Four industrial yeast strains (two ale and two lager strains) were exposed to oxidative stress in the form of H2O2 (5 mmol l−1) for two hours. Cell viability and occurrence of petites were determined by the slide culture and TTC‐overlay techniques, respectively. Increases in petite frequency were observed but only in those strains se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…A relevant parameter for fermentation performance is the number of respiratory‐deficient ‘petite’ cells accumulated during fermentation, particularly when re‐using (repitching) yeasts for consecutive fermentations. These cells contribute to off‐flavour production and reduced fermentation (Gibson et al ., ). Remarkably, one of the BC strains generated in our study was significantly reduced in petite formation and also showed a higher survival rate at the end of fermentation.…”
Section: Discussionmentioning
confidence: 97%
“…A relevant parameter for fermentation performance is the number of respiratory‐deficient ‘petite’ cells accumulated during fermentation, particularly when re‐using (repitching) yeasts for consecutive fermentations. These cells contribute to off‐flavour production and reduced fermentation (Gibson et al ., ). Remarkably, one of the BC strains generated in our study was significantly reduced in petite formation and also showed a higher survival rate at the end of fermentation.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, for heteroallelic strains containing dominant mutations, it is possible that replication stalling by mutant Mip1 itself causes oxidative damage on mtDNA, which can partially block replication by wt Mip1. Independently of the mechanisms, it is known that there is a correlation between mtDNA extended mutability and oxidative stress: petite frequency is higher in strains with a reduced antioxidant potential [66], in strains treated with hydrogen peroxide [67] and in strains deleted both in MSH1 and in OGG1 , encoding the mitochondrial glycosylase/lyase that specifically excises 8-oxo-dG residues in mtDNA [68].…”
Section: Discussionmentioning
confidence: 99%
“…ROS can damage a variety of cellular components, including DNA, proteins and unsaturated lipids [11]. ROS can damage the mitochondria causing the formation of respiratory-deficient petites [12-14]. ROS has been shown to have a direct role in cellular aging [15], replicant life-span has been related to anti-oxidant potential of the cell and the number of re-pitches into a fermentation [16,17].…”
Section: Introductionmentioning
confidence: 99%